2015
DOI: 10.1177/1077801215573332
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Options Available for Victims of Physical Intimate Partner Violence in Northern India

Abstract: We used qualitative methodologies to understand perceptions regarding options available for victims of physical intimate partner violence (IPV) in northern India. We interviewed male and female community members along with IPV experts. Interviews were transcribed, coded, and analyzed using grounded theory. Participants emphasized that a victim of physical IPV should bear the violence, modify her husband's behaviors, or seek help from her natal family. Accessing external resources such as the police or nongover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 24 publications
5
46
0
Order By: Relevance
“…Indeed, this is often considered the only viable strategy due to lack of independent resources and social and economic security. Similar findings have been noted in studies in India and Pakistan, where survivors of IPV emphasized the necessity to endure or ‘bear’ the violence (36, 37). …”
Section: Discussionsupporting
confidence: 86%
“…Indeed, this is often considered the only viable strategy due to lack of independent resources and social and economic security. Similar findings have been noted in studies in India and Pakistan, where survivors of IPV emphasized the necessity to endure or ‘bear’ the violence (36, 37). …”
Section: Discussionsupporting
confidence: 86%
“…Research witness of women being afraid to go to the police because they lack knowledge of the police and some even think that they will be arrested themselves. Perceptions that the police will tell the woman to modify her behaviour instead of trying to make the husband stop being violent seem to be common [26]. Attitudes to IPV among police officers need to be addressed and education in how to respond to IPV is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Participants perceived that an abused woman who seeks help from the police will be told to modify her behaviour, something that some participants themselves agreed with. Others were scared of the police because they did not know much about them [26]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that women are less educated, and pregnant with husbands who drink alcohol have higher risks to domestic violence [8][9][10][11][12][13][14][15][16]. Women who are less empowered, resides in rural areas and married to husbands who are from abusive homes, thus, ever experienced their father beating their mothers stands higher risks of domestic violence [10,15,[17][18][19][20][21][22][23][24]. Conversely, several literature evidenced that higher educational level for both women and men (husbands), women from wealthy families, empowered women and residing in urban areas were protective factors against domestic violence [11-13, 15, 19, 21, 25, 26].…”
Section: Introductionmentioning
confidence: 99%